The Effect Of Work Experience And Compensation On Employee Performance With Work Motivation As An Intervening Variable In BPJS Ketenagakerjaan North Medan Branch Office And Kisaran Branch Office - Priskanta Br Tarigan; Mesra B (Yayasan Multidimensi Kreatif, 2024)
Human resources play an important role in determining the success of a company. BPJS Ketenagakerjaan, as a public legal entity responsible for the social protection of workers in Indonesia, recognizes the importance of employee performance in achieving its goals. This study examines the influence of work experience, compensation, and motivation on the performance of BPJS Employment employees. Work experience is believed to improve employees' mindsets, attitudes, and skills. Fair and appropriate compensation is considered a form of reward for employee performance and service, which can ultimately increase work motivation. Motivation, which is influenced by individual and organizational factors, encourages employees to work optimally and achieve the targets that have been set. This study aims to analyze how these three factors, namely work experience, compensation, and motivation, individually and together, contribute to improving employee performance and achieving BPJS Employment goals. The results of this study are expected to provide recommendations for BPJS Ketenagakerjaan in optimizing human resource management and improving employee performance.